Effects of curriculum alignment, professional development, and access and resources on teaching strategies for museum education / Luo Junjie ... [et al.] - Junjie, Luo; Swaran Singh, Charanjit Kaur; Eng, Tek Ong; Yan, Li; Zhou, Wang; Zhifeng, Guo; Pan, Qian (Universiti Teknologi MARA, 2024)
Despite government efforts to promote museum awareness in education in China, little evidence exists on why there is a teaching gap in this discipline. This study explores factors contributing to this gap and classifies the levels of curriculum alignment, professional development, access, and resources among museum educators, along with their teaching strategies. The independent variables include curriculum alignment, and access and resources. Data were collected from 75 respondents in Guizhou Province, China. Data were analysed using descriptive statistics that involved estimating mean and standard deviation and also inferential statistics using two-way MANOVA and two-way ANOVA. Findings reveal high levels of curriculum alignment and access and resources but moderate levels of professional development. Teaching strategies for museum curriculum were reported at a high level overall. Significant difference was found in alignment, and access and resources based on gender, with female educators exhibiting higher alignment and access and resources but lower professional development compared to males. Significant interaction impact was found between educatos’ gender and experiences towards the teaching strategies for museum curriculum (F=25.111; p=0.000; p <0.05). Hence, policy makers and curriculum developers are urged to propose selected attributes of teaching that enhance the promotion of museum to the students and the public at large. Policy makers should consider targeted teaching attributes to enhance museum promotion to students and the public.